Right-wing authoritarianism, social dominance orientation, empathy, and materialistic value orientation as predictors of Intergroup prejudice in Argentina - Díaz Lázaro, Carlos (2014)
The study of individual differences in prejudice has received significant attention in the psychological literature. However, very little research has been published on Latin American countries. To address this gap, 300 residents from the general population in Mar del Plata, Argentina, were surveyed. The main objective of the study was to assess the contributions of right-wing authoritarianism (RWA), social dominance orientation (SDO), empathy, and materialistic value orientation (MVO) to the prediction of ethnic prejudice, heterosexism, hostile sexism, and benevolent sexism after controlling for impression management and socio demographic factors. Multiple regression analyses identified RWA as the most relevant variable predicting intergroup prejudice; as it contributed to the prediction of all dependent variables. The contributions of SDO, empathy, and MVO depended on the specific type of prejudice assessed. SDO and empathy made a significant statistical contribution to the prediction of ethnic prejudice and heterosexism; while a materialistic value orientation contributed only to the prediction of hostile sexism.